Synergistic Combination of Linezolid and Fosfomycin Closing Each Other’s Mutant Selection Window to Prevent Enterococcal Resistance - Jiang, Lifang; Xie, Na; Chen, Mingtao; Liu, Yanyan; Wang, Shuaishuai; Mao, Jun; Li, Jiabin; Huang, Xiaohui (Frontiers in Microbiology, 2021)
Enterococci, the main pathogens associated with nosocomial infections, are resistant to many common antibacterial drugs including β-lactams, aminoglycosides, etc. Combination therapy is considered an effective way to prevent bacterial resistance. Preliminary studies in our group have shown that linezolid combined with fosfomycin has synergistic or additive antibacterial activity against enterococci, while the ability of the combination to prevent resistance remains unknown. In this study, we determined mutant prevention concentration (MPC) and mutant selection window (MSW) of linezolid, fosfomycin alone and in combination including different proportions for five clinical isolates of Enterococcus and characterized the resistance mechanism for resistant mutants. The results indicated that different proportions of linezolid combined with fosfomycin had presented different MPCs and MSWs. Compared with linezolid or fosfomycin alone, the combination can restrict the enrichment of resistant mutants at a lower concentration. A rough positive correlation between the selection index (SI) of the two agents in combination and the fractional inhibitory concentration index (FICI) of the combination displayed that the smaller FICI of linezolid and fosfomycin, the more probable their MSWs were to close each other. Mutations in ribosomal proteins (L3, L4) were the mechanisms for linezolid resistant mutants. Among the fosfomycin-resistant mutants, only two strains have detected the MurA gene mutation related to fosfomycin resistance. In conclusion, the synergistic combination of linezolid and fosfomycin closing each other’s MSW could effectively suppress the selection of enterococcus resistant mutants, suggesting that the combination may be an alternative for preventing enterococcal resistance. In this study, the resistance mechanism of fosfomycin remains to be further studied.